2019
DOI: 10.1002/cche.10192
|View full text |Cite
|
Sign up to set email alerts
|

Effect of incorporation of germinated flour and protein isolate from chickpea on different quality characteristics of rice‐based noodle

Abstract: Background and objectivesNoodles from rice are consumed in most of the Asian countries due to ease in preparation and good consumer acceptability. So, the present study was designed to develop protein‐enriched noodles from rice flour and chickpea (germinated flour from 7% to 30% and protein isolate from 3% to 10%) and to investigate their physicochemical, cooking, rheology, electrophoretic properties, in vitro starch and protein digestibility and sensory evaluation.FindingsThe present study was carried out to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…These results concur with our previous study on faba bean supplemented pasta where we found that medium B1-chains [degree of polymerization (DP), [13][14][15][16][17][18][19][20][21][22][23][24] showed positive correlation with RS in raw starch samples but showed no correlation in the cooked pasta [15]. Pasta is consumed after cooking while ready to eat crackers require no further processing.…”
Section: Correlation Between Cracker Meal Components and Digestibilit...supporting
confidence: 92%
See 1 more Smart Citation
“…These results concur with our previous study on faba bean supplemented pasta where we found that medium B1-chains [degree of polymerization (DP), [13][14][15][16][17][18][19][20][21][22][23][24] showed positive correlation with RS in raw starch samples but showed no correlation in the cooked pasta [15]. Pasta is consumed after cooking while ready to eat crackers require no further processing.…”
Section: Correlation Between Cracker Meal Components and Digestibilit...supporting
confidence: 92%
“…Pulses are consumed in different forms and levels across countries, ethnic groups and economic classes [ 23 ]. In Asian countries, pulses are traditionally consumed as whole grains or after splitting (dahl), but in the Western countries, pulse flours are used to partially substitute wheat flour in pasta, bread and bakery products [ 15 , 23 , 24 , 25 , 26 ]. However, utilization of pulses to enhance the nutritional value of wheat-based products presents specific challenges for consumer acceptance that is dependent on texture, flavor, appearance, and color [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The dough sections were stained with a mixture of fluorescein isothiocyanate (FITC, 0.0001%) and Rhodamine B (0.001%, w/v) in N,N‐dimethylformamide to visualize starch (FITC, green) and proteins (Rhodamine B, red) under a FluoView FV300 confocal laser scanning microscope (Olympus Corp., Tokyo, Japan). Stained slides were stored at ambient temperature for 20 min, washed with distilled water to remove extra dye, and then cover slips were mounted to prevent water loss (Sofi, Singh, Chhikara, & Panghal, ). The excitation/emission wavelengths were 488 nm/518 nm for FITC and 568 nm/625 nm for Rhodamine B, and all samples were observed at high magnification to provide the best characterization of the microstructure.…”
Section: Methodsmentioning
confidence: 99%
“…The cooking characteristics of fresh noodles were evaluated according to the method described by Sofi et al. (). The optimum cooking time for each sample was determined using the AACC International Method (44‐15.02 Moisture Air‐Oven Methods AACC, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…Cold extrusion is an ideal process to produce pasta fortified with legumes, although this fortification is a new process. The principal studies in the literature showed the fortification of wheat flour with legumes such as soya, pea, lentil, chickpea, lupin and bean [ 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 ]. These authors revealed the modifications observed in the pastas fortified in comparison to the control pasta (in general, durum wheat semolina).…”
Section: Effect Of Cold Extrusion On the Bioactive Compounds Of Pumentioning
confidence: 99%